Phage-displayed peptides targeting specific tissues and organs. (3rd July 2019) - Andrieu, Josu; Re, Francesca; Russo, Laura; Nicotra, Francesco
Abstract: Phage display is a powerful and widely used technique to find novel peptide ligands. A massive amount of peptide sequences have been identified for all kinds of materials, and peptides that may have targeting capabilities towards specific cells and tissues have received special attention in biomedical sciences. As a result, it is increasingly harder to follow all the work that has been done, which sometimes leads to many promising ligands receiving little attention, together with the publication of false positives that have already been found. The aim of this review is to provide an updated and comprehensive list of phage-displayed peptides targeting different tissues and organs. The limitations of the technique are carefully analysed and the future perspectives envisaged.